Review of the pteraspidiform heterostracans (Vertebrata, Agnatha) from the Devonian of Podolia, Ukraine, in the Theodor Vascautanu collection, Bucharest, Romania - Dumbrava, Mihai; Blieck, Alain (HAL CCSD, 2005)
The pteraspidiform heterostracans are jawless vertebrates known from the Pridolian (Upper Silurian) to the Givetian (Middle Devonian). This preliminary study focuses on the redetermination and restudying of the material collected in 1931 by Vascautanu from the Devonian formations from the former Romanian bank of the Dniester river, figured by Pauca in 1938. The material comes from the following collections: University of Bucharest Laboratory of Palaeontology and the National Geological Museum. The redetermination of the material is based on the study of the orbito-pineal region; biometric data and overall morphology and shape of the plates. The identification of the material follows the criteria presented by Blieck (1984) for his systematic, phylogenetic and biostratigraphic review of the pteraspidiform heterostracans from Great Britain, Podolia, Spitzbergen and the Ardenne Massif. Given the progres made in the study and of fossil agnathans, and also the fact that from 1938 until the present no study has been carried out on the material collected by Th. Vascautanu, the present review aims to show for the first time part of the ostracoderm diversity from the former Romanian part of Podolia.